Fabrication of Biobriquettes from Mixture of Palm Fronds and Palm Shells with Varying Binders of Tapioca and Sago Flour - Simatupang, Dimas Frananta; Simbolon, Merta (MultiTech Publisher, 2023)
Biobriquettes are products obtained from the compaction process of biomass residue used as fuel and formed by using a binding agent. In this study, the biomass used comprised palm fronds and palm shells. The objective was to determine the characteristics of biobriquettes. The research methodology adopted was quantitative experimentation. Results showed that the highest calorific value of biobriquettes was 6729.92 cal/g (1:3-sago 15%), the lowest moisture content was 1.1168% (1:3-tapioca 10%), the lowest ash content was 9.5232% (1:3-sago 10%) and the highest density was 0.9927 g/cm3 (1:3-tapioca 20%). Based on the test results, it can be concluded that the optimal ratio of raw materials palm fronds to palm kernel shells for biobriquette fabrication is 1:3 with 10% tapioca flour and 10-15% sago flour as binders.